(untitled) (Research, Society and Development, 2019)
Institutional evaluation through external community participation is an important tool for the verification and monitoring of aspects related to higher education institutions. In this context, the article discloses an extension project that aimed to assist in the self-assessment of a university. The purpose of this paper is to record the work that was done at the University and at the same time to contribute to the debate about teaching and extension in engineering. The work focused on the construction of an Itinerant Totem built by engineer students. To this end, the project members defined the goals for the development of software to be used in the research, the plan for making the Totem’s physical structure and the places to be visited in order to perform data collection. The content of the questions on the form included information about the participant’s age, infrastructure, accessibility, and safety at the university. Upon completion of the goals set for Totem creation, research can be conducted at five university locations. Given the results obtained after the research using Totem, there was a significant increase in the number of participants from various segments, which contributed to the broader scope of institutional evaluation and may promote improvements within the University. Moreover, it is noteworthy that for the students involved, it was an application of the knowledge acquired in their undergraduate engineering courses.